Cultural and national specifics of the Basque language world view - Yu V Fernandez Sanchez (RUDN Journal of Language Studies, Semiotics and Semantics, 2016)
In the article we analyze the particularities of the language awareness proper to representatives of the Basque linguistic culture and try to characterize their cultural and national identity. The anthropocentric orientation of modern linguistics is of genuine interest for many researchers who investigate the language as a key to the ethnic identity, meanwhile the expansion of intercultural contacts in an era of increasing globalization explain the relevance of the chosen theme. Identification of the specific features of different linguocultures allows us to make good the deficit of didactic material necessary to optimize cross-cultural communication. The investigation of the Basque linguistic culture assumes great practical importance, since this European ethnic group is one of the most mysterious one not only in the anthropological aspect, but also in the linguistic context. The origin of the Basque people and their language “euskera” still remains one of the most intriguing topics of European linguistics and ethnology, and therefore involves a wide range of possible future research.